(untitled) (Research, Society and Development, 2020)
The marketing of vegetables in natura can be limited by physical, physiological and even biological defects. Therefore, the objective was to evaluate the quality, commercialization and post-harvest loss of beet in different commercial segments of Chapadinha (MA). The research was carried out through the application of questionnaires in 20 establishments, which included free markets, supermarkets and greens. The interviews covered questions related to price, volume offered, quality, consumption and beet post-harvest losses. The quality characterization was done through the collection of 30 samples per segment, in which the weight with peel, weight without peel, length, diameter and soluble solids were measured. It was concluded that supermarkets present the best quality attributes, in terms of length (8.15 cm), diameter (7.3), weight with and without peel (228.56g and 205.34 g, respectively), as well as the most accessible price (R 3.25). As for losses, the main causes are physiological disorders and mechanical damages. The fair has the highest percentage of post harvest losses (16,11%), followed by vegetables (5,49%) and supermarkets (2,41%). It is important the adoption of good post-harvest practices and management to improve the quality of products offered, prices practiced and reduction of beet losses.